Wartime interpreting during the Sino-Dutch War (1661–1662) - Chang, Pin-ling (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
While wartime interpreting has become a research focus in very recent years, little research has explored on-the-battleground interpreting for warring sides in pre-modern times. By examining the Dutch East India Company (VOC) archival resources and other relevant historical documents, this study discusses interpreting practices during the Sino-Dutch War (1661–1662) in seventeenth-century colonial Taiwan, with a focus on interpreters’ backgrounds, functions and status, issues of loyalty and trust, and interpreters and translation as a tool of manipulation and power struggles. The overview of the interpreters and the interpreting practices in pre-modern wartime viewed against our present experience shows both differences and similarities in wartime interpreting between the past and the present; it also indicates that although the importance of interpreters has been increasingly recognized, they have remained a symbol of both relief and distrust since ancient times.